Microemulsion a Chemical Nanoreactor - Mejuto, Juan C. (IntechOpen, 2019)
This book aims to provide readers with some of the current trends in microemulsions as scalable chemical nanoreactors. The chapters include discussions on microemulsions as reaction media, taking advantage of both the special behavior of trapped water inside their microdroplets and their potential use as a template for nanomaterials. The information contained in this book covers topics that will be of interest to students and researchers in physical chemistry, chemical engineering, and material science. In addition, this book will serve as a tribute in memoriam to Prof. Julio Casado, Professor of Physical Chemistry at the Universities of Santiago de Compostela and Salamanca and Doctor Honoris Causa from the University of Vigo, who died on April 2, 2018. Sit tibi terra levis.